Simulation Series: Emergencies in Technology-Dependent Children - Neha Shah; Priti Bhansali; Michelle McGarry; Anjna Melwani; Olga Morozova; Kavita Parikh; Aisha Barber Davis (Association of American Medical Colleges, 2013)
Abstract Introduction Every pediatric health care professional has taken care of a child with special health care needs. Over the past several years, it is clear that the number of children with medical complexity has been rising as the survival rates of previously fatal conditions have improved. Technology-dependent children with special health care needs present a unique set of morbidities, some of which may be associated with malfunction of the very devices used to treat them. The purpose of these scenarios is to teach and allow rehearsal of an approach to some of the potentially life-threatening complications of technology used to treat medically-complex pediatric patients. Methods This is a series of four case scenarios that depict emergencies in technology-dependent, medically complex pediatric patients. The scenarios are designed for use in a variety of settings and do not require high fidelity simulation technology. The focus of each scenario is identification of the device-related problem and initial management and diagnostic work-up. Results These scenarios are being used within our Division of Hospital Medicine, a group of over 30 attending hospitalists and hospitalist fellows that serve in a variety of practice settings (community affiliates, an academic teaching center, and a subacute care facility). To date, we have had two sessions with hospitalists in our division that used all four of these simulation cases. For the 18 participants, to date, the average rating of the statement "The information and concepts addressed will change the way I practice," was 4.6 on a 5-point Likert scale. Comments from participants included "Interactive and educational" and "These topics are relevant to community hospitalists." Discussion In our experience, we have found that taking time to orient the participants is key to the success of the session. Specifically, being very clear about what equipment is available, manikin capabilities, expectations for their participation, and role of the facilitator all enhance the participant experience.